A polycomb group protein is retained at specific sites on chromatin in mitosis. - Follmer, N.E.; Wani, A.H.; Francis, N.J. (PLoS Genetics, 2012)
Epigenetic regulation of gene expression, including by Polycomb Group (PcG) proteins, may depend on heritable chromatin states, but how these states can be propagated through mitosis is unclear. Using immunofluorescence and biochemical fractionation, we find PcG proteins associated with mitotic chromosomes in Drosophila S2 cells. Genome-wide sequencing of chromatin immunoprecipitations (ChIP-SEQ) from mitotic cells indicates that Posterior Sex Combs (PSC) is not present at well-characterized PcG targets including Hox genes in mitosis, but does remain at a subset of interphase sites. Many of these persistent sites overlap with chromatin domain borders described by Sexton et al. (2012), which are genomic regions characterized by low levels of long range contacts. Persistent PSC binding sites flank both Hox gene clusters. We hypothesize that disruption of long-range chromatin contacts in mitosis contributes to PcG protein release from most sites, while persistent binding at sites with minimal long-range contacts may nucleate re-establishment of PcG binding and chromosome organization after mitosis.